Monopoli dalam Perspektif Ekonomi Islam - Fatah, Dede Abdul (Al-Iqtishad: Journal of Islamic Economics, 2012)
Monopoly in Islamic economic perspective means withholding or hoarding goods in purpose, especially in times of scarcity, with the goal of raising the price at a later date in order to obtain greater profits. Monopolistic practices is a type of violation will result in muamalah because market mechanism disrupted, so that producers will get a big profit (monopolistic rent), while the consumer due to the accumulation of actions will suffer and get loss. Therefore, this monopoly will bring people in general harmed by the act of a small group of monopolistic very unjust, selfish, and irresponsibleDOI: 10.15408/aiq.v4i2.2095